Nicotine dependence and intention to quit among electronic, conventional and dual cigarette users in Karachi - Abeeha Batool Zaidi; Shiraz Shaikh (Journal of the Pakistan Medical Association, 2022)
Objective: To compare nicotine dependence and intention to quit among different types of smokers. Method: The comparative cross-sectional study was conducted from November 2018 to October 2019 in Karachi after approval from the ethics review committee of the Jinnah Sindh Medical University, and comprised conventional, electronic and dual cigarette users. Data was collected using a structured questionnaire regarding socio-demographics, usage characteristics, and intention to quit. The validated Hooked on Nicotine Checklist was also used. Data was analysed using SPSS 22. Results: Of the 246 subjects, 82(33%) were conventional cigarette users with a mean age of 27.41±8.7 years, 82(33.3%) were electronic cigarette users having mean age of 30.37±9.16 years, and 82(33.3%) were dual cigarette users with a mean age of 28.89±9.07 years. The use of electronic cigarette was more in people with higher age (p=0.01), married (p=0.001) and having higher income (p=0.05). Compared to conventional cigarette users, electronic cigarette users showed lower odds of high nicotine dependence (odds ratio: 0.38, 95% confidence interval: 0.18-0.80). No significant difference was observed in intention to quit among different types of cigarette users (p>0.05). Conclusion: Electronic cigarettes users were comparatively less nicotine-dependent compared to the users of other types of cigarettes. Electronic cigarettes should only be recommended to conventional users with the intention to quit. Key Words: Cigarette, Electronic, Nicotine dependence, Quit intention.